Cyanoacrylate closure for peripheral veins: Consensus document of the Australasian College of Phlebology. (April 2020) - Parsi, Kurosh; Roberts, Stefania; Kang, Mina; Benson, Stephen; Baker, Luke; Berman, Ivor; Bester, Lourens J; Connor, David E; Dinnen, Paul; Grace, Joseph; Stirling, Andrew; Ibrahim, Nabeel; et al.
Background: Cyanoacrylates are fast-acting adhesives used in procedural medicine including closure of superficial wounds, embolization of truncal vessels pre-operatively, vascular anomalies, visceral false aneurysms, endoleaks, gastrointestinal varices and gastrointestinal bleeding. More recently, catheter-directed cyanoacrylate adhesive closure was introduced as an alternative to endovenous thermal ablation (ETA) to occlude superficial veins of the lower limbs. Objectives: To formulate policies for the safe and effective delivery of cyanoacrylate adhesive closure procedures in Australasia, based on current experience and evidence. Methods: A panel of phlebologists including vascular surgeons, interventional radiologists, dermatologists and research scientists systematically reviewed the available data on cyanoacrylate products used in medicine and shared personal experience with the procedure. The reviewed material included bibliographic and biomedical data, material safety data sheets and data requested and received from manufacturers. Results and recommendations: Cyanoacrylate adhesive closure appears to be an effective treatment for saphenous reflux with occlusion rates at 36 months of 90–95%. We recommend a maximum dose of 10 mL of cyanoacrylate per treatment session. Serious complications are rare, but significant. Hypersensitivity to acrylates is reported in 2.4% of the population and is an important absolute contraindication to cyanoacrylate adhesive closure. 1 Post-procedural inflammatory reactions, including hypersensitivity-type phlebitis, occur in 10–20% of patients. 2 In the long term, cyanoacrylate adhesive closure results in foreign-body granuloma formation within 2–12 months of the procedure. We recommend against the use of cyanoacrylate adhesive closure in patients with uncontrolled inflammatory, autoimmune or granulomatous disorders (e.g. sarcoidosis). Caution should be exercised in patients with significant active systemic disease or infection and alternative therapies such as thermal ablation and foam sclerotherapy should be considered. Conclusions: Cyanoacrylate adhesive closure appears to be an effective endovenous procedure, with short-term closure rates comparable to ETA and therefore greater efficacy than traditional surgery for treating superficial veins of the lower limbs. Ongoing data collection is required to establish the long-term safety.